2004
DOI: 10.1158/1078-0432.ccr-03-0067
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Kidney Cancer-Specific Antitumor Immune Responses Using Peripheral Blood Monocytes Transduced With a Recombinant Adenovirus Encoding Carbonic Anhydrase 9

Abstract: Purpose: Carbonic anhydrase 9 (CA9) is the most promising molecular marker described for renal cell carcinoma (RCC) to date. We investigated whether transduction of monocytes from peripheral blood with adenovirus encoding the CA9 gene (AdV-CA9) could stimulate a T-cell mediated immune response against cancer cells expressing CA9. The ability to consistently generate a T-cell response is an important step toward the development of a CA9-specific RCC vaccine.Experimental Design: AdV-CA9 was generated using the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Although the highest level of CA II expression was noted in chromophobe RCCs, several clear cell RCCs expressed this gene, suggesting that, at least at the RNA level, there is overlap between the two types of RCCs (8). Interestingly, CA IX expression was specific for RCCs compared with normal renal tissue, confirming that this gene may be a better target for drug or immune therapy (32). Interestingly, the expression of CA IX was shared by other primary epithelial cancers but not melanoma metastases, suggesting that the expression of this gene is at least partly associated with oncogenesis and that it may not be solely responsible for the immune responsiveness of these diseases to immune therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Although the highest level of CA II expression was noted in chromophobe RCCs, several clear cell RCCs expressed this gene, suggesting that, at least at the RNA level, there is overlap between the two types of RCCs (8). Interestingly, CA IX expression was specific for RCCs compared with normal renal tissue, confirming that this gene may be a better target for drug or immune therapy (32). Interestingly, the expression of CA IX was shared by other primary epithelial cancers but not melanoma metastases, suggesting that the expression of this gene is at least partly associated with oncogenesis and that it may not be solely responsible for the immune responsiveness of these diseases to immune therapy.…”
Section: Discussionmentioning
confidence: 94%
“…CAIX expression correlates with tumor stage, grade, lymph node involvement, distant metastasis, survival, and response to immunotherapy [158,159]. Overexpression of CAIX has been seen in 70% to 96% of clear cell renal cell carcinomas [160,161]. Followup study of 63 cases of clear cell renal cell carcinoma showed that metastasis-free survival rate correlates with intensity of CAIX expression and is significantly better for patients whose tumors highly express CAIX as compared with patients whose tumors express it less strongly [157].…”
Section: Carbonic Anhydrase IXmentioning
confidence: 99%
“…In most cancers, CAIX is a marker for hypoxia with expression increased in bulky tumours and greatest expression in tumour cells immediately adjacent to areas of necrosis [6]. However, in clear cell RCC (ccRCC), CAIX expression is overexpressed due to inactivation of the VHL gene product and as a result overexpression of HIF-1a, a transcription factor for CAIX [7].In ccRCC, CAIX is an ideal biomarker that establishes diagnosis [8-10], determines prognosis [11][12][13][14], predicts treatment response [15,16] and serves as a target for therapy [17][18][19]. CAIX is a good biomarker for RCC (detected in 86% of RCC samples and only 9% of normal kidney [20], and present in more than 80% of primary and metastatic RCC [21]), and ccRCC in particular (94-100% of ccRCC stained positively for CAIX [12,21], whereas staining was absent in benign tumours such as oncocytoma [12]) (Fig.…”
mentioning
confidence: 99%